Development of Economic Performance of Small and Medium – sized Enterprises in the Slovak Republic in the Context of the Impact of COVID - 19 - Belanová, Katarína, 1978-
Zhodnotenie ekonomickej výkonnosti MaSP v SR počas obdobia pandémie v rokoch 2019-2020.